Peran Elite Lokal Dalam Penggalangan Dukungan Politik (Studi Pada Tahapan Pemilihan Kepala Desa Periode 2023-2028 Di Desa Panggal-Panggal Kecamatan Semidang Aji Kabupaten Ogan Komering Ulu) - Rizki, Laura Selpia; Akhyar, Taufik; Azzuhri, Hatta (Journal of Innovative and Creativity, 2026)
Village head elections are a manifestation of local democracy that not only involve competition between candidates but are also influenced by the roles of powerful social actors at the village level. This study aims to analyze the role of local elites in garnering political support and understand the community's response to the influence of local elites on the village head election stages for the 2023-2028 period in Pangal-Panggal Village, Semidang Aji District, Ogan Komering Ulu Regency. This study uses a qualitative approach with descriptive methods. Data collection techniques were carried out through observation, in-depth interviews, and documentation. Informants in this study consisted of two influential local elites: the former head of Panggal-Panggal village for the 2004-2010 period, and a community leader who also served as a village elder and a member of the Panggal-Panggal village community. To strengthen the data on village government assistance, he also served as an informant in this study. Data analysis was conducted using the Miles and Huberman model using role theory and political support theory as an analytical framework. This study uses a qualitative approach with descriptive methods. Data collection techniques were carried out through observation, in-depth interviews, and documentation. Informants in this study consisted of two influential local elites: the former head of Panggal-Panggal village for the 2004-2010 period, and a community leader who also served as a village elder and a member of the Panggal-Panggal village community. To strengthen the data on village government assistance, he also served as an informant in this study. Data analysis was conducted using the Miles and Huberman model using role theory and political support theory as an analytical framework.